Judicial Reasoning in Cumulative Divorce and Child Custody Cases Involving Financial Neglect: A Case Study of Decision No. 5139/Pdt.G/2020/PA.Tgrs - Johan Katamsyah; Amin Songgirin (Journal of Islamic Law and Legal Studies, 2025)
This study analyzes the judicial reasoning in a cumulative family law case involving a wife’s petition for divorce and child custody due to her husband’s failure to provide financial support. Using a normative-empirical legal research method, the research focuses on case No. 5139/Pdt.G/2020/PA.Tgrs at the Tangerang Religious Court. The findings reveal that the court acknowledged economic neglect as a legitimate ground for divorce and upheld maternal custody for the underage child based on Article 105 of the Compilation of Islamic Law. The judge’s decision also reflected a balanced approach between formal legal provisions and Islamic ethical principles such as maslahah (public interest) and justice. This dual reasoning framework enhances both the legal legitimacy and moral authority of the religious courts. The research contributes to the discourse on integrated legal reasoning in pluralistic systems and highlights the importance of protecting women and children's rights in family law proceedings.